2013
DOI: 10.1088/0004-637x/773/1/3
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Between Star Formation Rate and Average Black Hole Accretion in Star-Forming Galaxies

Abstract: We present a measurement of the average supermassive black hole accretion rate (BHAR) as a function of star formation rate (SFR) for galaxies in the redshift range 0.25 < z < 0.8. We study a sample of 1,767 far-IR selected star-forming galaxies in the 9 deg 2 Boötes multiwavelength survey field. The SFR is estimated using 250 µm observations from the Herschel Space Observatory, for which the contribution from the AGN is minimal. In this sample, 121 AGNs are directly identified using X-ray or mid-IR selection c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
198
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 91 publications
22
198
1
Order By: Relevance
“…8.3). This is in agreement with scenarios where both the intense SF activity and the efficient accretion on the black hole are triggered by gas rich major mergers (e.g., Chen et al 2013;Symeonidis et al 2013). …”
Section: Discussionsupporting
confidence: 89%
“…8.3). This is in agreement with scenarios where both the intense SF activity and the efficient accretion on the black hole are triggered by gas rich major mergers (e.g., Chen et al 2013;Symeonidis et al 2013). …”
Section: Discussionsupporting
confidence: 89%
“…Thus, the weak observed correlation between star formation and BH accretion might be attributed to the timescale difference between the AGN accretion efficiency and star formation variability (e.g. Mullaney et al 2012b;Chen et al 2013;Hickox et al 2014).…”
Section: The Star Formation Dependence On Agn Activitymentioning
confidence: 99%
“…Lutz et al 2008;Serjeant & Hatziminaoglou 2009;Bonfield et al 2011;Silverman et al 2009;LaMassa et al 2013), some others found a strong correlation (e.g. Hao et al 2005;Satyapal et al 2005;Netzer 2009;Shi et al 2009;Chen et al 2013a) whereas others (e.g. Harrison et al 2012;Rosario et al 2012;Rovilos et al 2012;Mullaney et al 2012;Bongiorno et al 2012) found a flat relationship (or no evidence for a correlation).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, instead of concentrating on individual sources and instantaneous AGN activity, averaging the AGN luminosity over the populations should provide a clearer view of the relation between SFR and AGN activity (e.g. Chen et al 2013a).…”
Section: Introductionmentioning
confidence: 99%